Increased levels of exhaled carbon monoxide in bronchiectasis: a new marker of oxidative stress. Issue 10 (1st October 1998) - Horvath, I; Loukides, S; Wodehouse, T; Kharitonov, S A; Cole, P J; Barnes, P J
Abstract : BACKGROUND: Bronchiectasis is a chronic inflammatory lung disease associated with increased production of oxidants due mostly to neutrophilic inflammation. Induction of heme oxygenase (HO-1) by reactive oxygen species is a general cytoprotective mechanism against oxidative stress. HO-1 catabolises heme to bilirubin, free iron and carbon monoxide (CO). Exhaled CO measurements may therefore reflect an oxidative stress and be clinically useful in the detection and management of inflammatory lung disorders. METHODS: The levels of exhaled CO of 42 non-smoking patients with bronchiectasis treated or not treated with inhaled corticosteroids were compared with CO levels in 37 normal non-smoking subjects. RESULTS: Levels of exhaled CO were raised in patients with bronchiectasis, both those treated with inhaled corticosteroids (n = 27, median 5.5 ppm, 95% CI 5.16 to 7.76) and those not treated with inhaled corticosteroids (n = 15, median 6.0 ppm, 95% CI 4.74 to 11.8), compared with normal subjects (n = 37, median 3.0 ppm, 95% CI 2.79 to 3.81, p = 0.0024). There was no correlation between exhaled CO and HbCO levels ( r = 0.42, p = 0.12) in normal subjects (n = 7), nor between the urine cotinine concentration and exhaled CO levels ( r = 0.2, p = 0.12). CONCLUSIONS: Increased levels of exhaled CO may reflect induction of HO-1 and oxidative stress in bronchiectasis. Measurement of exhaled CO may be useful in the management of bronchiectasis and possibly other chronic inflammatory lung disorders.